HISTORY OF THE CREATION OF THE SCIENTIFIC SOCIETY OF ANATOMISTS, HISTOLOGISTS, EMBRYOLOGISTS AND TOPOGRAPHIC ANATOMISTS OF UKRAINE - Chaikovsky, Yu.B.; Raskaliei, V.B.; Raskaliei, T.Ya.; Appelhans, O.L.; Pivtorak, V.I.; Shepitko, V.I. (World of Medicine and Biology, 2022)
The Scientific Society of Anatomists, Histologists, Embryologists and Topographic Anatomists (SS AHET) of Ukraine is an independent scientific organization of morphologists of Ukraine. Its historical development dates back to 1953. It was then that famous Ukrainian scientists initiated the separation from the All-Union Scientific Society of Anatomists, Histologists and Embryologists (AUSS AGE). Many steps were taken on the way to the formation of SS AHET of Ukraine. Many scientific and organizational achievements replenished the coffers of the society, the main goals of which are and will be the popularization of science in Ukraine and the development of international relations with European scientists. With this work, we begin a cycle of articles on the main historical moments of the formation of SS AHET, focusing on well-known Ukrainian scientists who made significant efforts to develop morphology in Ukraine and the world.